PENERAPAN PENDEKATAN SAINTIFIK MODEL PROBLEM BASED LEARNING DALAM PEMBELAJARAN PAI - Rohmadi Rohmadi (PAI RAFAH, 2019)
This research is underpinned by some related problems of the scientific approach application of formulated based on the 2013 curriculum, especially the scientific approach of problem based learning in the Islamic Education of VII grade students at SMPN 1 Ngaglik Yogyakarta. The problem to study in the research is the planning, application, and evaluation of scientific model approach of problem based learning in the Islamic Education learning process. This research was conducted qualitatively through descriptive approach. The research is targeted towards the Islamic Education teachers of SMPN 1 Ngaglik as the research subjects. The research object is the implementation of scientific model approach of problem based learning of the Islamic Education learning process. The data were analyzed through interactive model of Miles and Huberman comprised of data condensation, data display, and conclusion drawing/ verification. The research reveals that (1) The learning implementation of Islamic Education at VII grade of SMPN 1 Ngaglik is already based on the syllabus of and Lesson Plan determined by Permendikbud of Indonesian Republic Number 22 Year 2016, (2) The Learning implementation of Islamic Education at VII grade of SMPN Ngaglik has met the standardized scientific model approach of problem based learning in that teachers have implemented the learning stages as written in the scientific model of problem based learning comprehensively. However, it turns out that (3), the evaluation used has not met the criteria of authentic assessment of 2013 curriculum since the Islamic Education teachers of VII grade students of SMPN Ngaglik did not conduct journal assessment.